The epistemology of the value of aqidah akhlaq education in Biyanglala poetry book by Abdul Wachid B.S. (A semiotic study) - Metros Prihatin; Heru Kurniawan; Adi Purnomo (Universitas Ahmad Dahlan, 2021)
The purpose of this paper is to analyze and describe the value of aqidah akhlaq education in Abdul Wachid B.S.’s poems especially in Biyanglala. The method used in this research was qualitative research method of library research where the data collection technique is carried out by studying the reading in the form of lecture notes, books, literature and regulations related to the problem under study. The object of research in this paper is the Biyanglala poetry book. To analyze and describe the value of aqidah akhlaq education in the poetry book, the writer uses Michael Riffaterre's semiotics. According to the results of the study, the writers found out that Biyanglala poetry book by Abdul Wachid B.S.’s contained the value of aqidah akhlaq education, namely in the poetry